HABITS OF PHYSICAL ACTIVITY IN THE PIONEERING GROUPS OF INTEGRATED TECHNICIAN EDUCATION OF CEFET-PARAÍBA (Fiep Bulletin - online, 2013)
The objective of this work is to describe characteristics of the practice of Physical Activity(AF) at leisure, of the three pioneering groups of the first year of Integrated Technician Education, in CEFET-PB. It was used, as instrument of measure, autoadministrative questionnaire. It was applied the descriptive, inferential statistics and analysis of correspondence. The most relevant results show that the pupils practise vigorous and moderate AF, from 1 to 2 times a week. We conclude that students dedicate great part of their leisure time to passive activities. The bigger the familiar income, the bigger the change of pro-active behaviour.
Keywords: Integrated Technician Education; Physical activity; Leisure